A simple Ultraviolet spectrophotometric method for the determination of etoricoxib in dosage formulations. - S Singh; A Mishra; A Verma; Ashoke K Ghosh; Arun K Mishra (Wolters Kluwer Medknow Publications, 2012)
The present study was undertaken to develop a validated, rapid, simple, and low-cost ultraviolet (UV) spectrophotometric method for estimating Etoricoxib (ETX) in pharmaceutical formulations. The analysis was performed on Î max 233 nm using 0.1 M HCl as blank/diluent. The proposed method was validated on International Conference on Harmonization (ICH) guidelines including parameters as linearity, accuracy, precision, reproducibility, and specificity. The proposed method was also used to access the content of the ETX in two commercial brands of Indian market. Beer's law was obeyed in concentration range of 0.1-0.5 Î¼g/ml, and the regression equation was Y = 0.418x + 0.018. The mean accuracy values for 0.1 Î¼g/ml and 0.2 Î¼g/ml concentration of ETX were found to be 99.76 Â± 0.52% and 99.12 Â± 0.84, respectively, and relative standard deviation (RSD) of interday and intraday was less than 2%. The developed method was suitable and specific to the analysis of ETX even in the presence of common excipients. The method was applied on two different marketed brands and ETX contents were 98.5 Â± 0.56 and 99.33 Â± 0.44, respectively, of labeled claim. The proposed method was validated as per ICH guidelines and statistically good results were obtained. This method can be employed for routine analysis of ETX in bulk and commercial formulations.